Penerapan Senam Ergonomik Terhadap Penurunan Tekanan Darah Lansia Penderita Hipertensi - Nuar Pilarnanti, Viary; Husain, Fida' (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background; Hypertension in the elderly increases every year, in Pacitan Regency there are 6,211 people, in Nawangan District there are 1,290 people with hypertension and in Sempu Village there are 87 elderly people with hypertension. The cause of high hypertension is influenced by lifestyle, scale factors and environmental factors, and if not immediately overcome it will cause premature death and disability rates for sufferers.Purpose; Knowing changes in blood pressure in elderly people with hypertension before and after the application of ergonomic gymnastics. Method; This application is with descriptive research methods and observing an event. Descriptive research is research conducted to describe or describe an event that occurs in society. Result; The results of blood pressure measurements before ergonomic exercise were carried out on the two respondents, namely Mrs.T with a blood pressure of 165/90 mmHg and Mrs. W with a blood pressure of 160/100 mmHg, both classified as having stage 2 hypertension or moderate hypertension.. The results of blood pressure measurements after ergonomic exercise on Mrs. T 150/80 mmHg and Mrs. W to 140/90 mmHg classified as stage 1 or mild hypertension.. Conclusion; This ergonomic exercise can lower blood pressure in elderly people with hypertension